Hand Gesture Controlled ARM - Mitra, Atreyee; Chatterjee, Sankhojjal; Bakshi, Shamik; Banerjee, Suvobroto (International Journal of Computer Sciences and Engineering, 2025)
Robotic hands so far made were done by usingmicrocontroller and were wired based. Though number of degrees of freedom can be increased as well as precision of the arm increases with the help of using microcontroller, but eventually the roboarm used to become costly. In this paper we have tried to make a Roboarm capable of enacting human hand gesture which is microcontrollerless and more over it is based on Wireless communication technique. For picking purpose we have used Servo Motors and for controlling the servos we used Servo driver using 555 Timer. Humans pick things up without thinking about the steps involved in it. In order for a robot or a robotic arm to pick up or move something, someone needs to tell it to perform several actions in a particular manner such as moving the arm, to rotating the “wrist” to opening and closing the “hand” or “fingers”.